A changing landscape of elderly care - Dahl, Hanne Marlene (Politica, 2019)
Elderly care is at the top of the political agenda nationally and globally due to changing demography, declining fertility rates, increasing labor market participation rates of women and the financial crisis. Elderly care has been theorized successfully within feminist care theory. However, changing societal and political conditions in the Nordic welfare regime such as professionalizing, late modernizing, degendering and neoliberalizing indicate the inadequacy of this theoretical framework. In critical dialogue with – and extension of – the feminist theory of care, I argue in favor of introducing new analytical concepts from philosophy and political science such as assemblage, relatedness, logics, multilevel governance and transnational discourses. These concepts are elaborated in view of the contemporary (human) condition.